Magnitude of nonadherence to diet and exercise recommendations and associated factors among type 2 diabetes patients on treatment follow-up at Asella Referral and Teaching Hospital, Arsi, Ethiopia: A cross sectional study - Nebyu Mekonen; Zewdu Hurisa; Enku Selamu; Tesfa G/meskel; Ayalneh Demissie (PLoS ONE, 2026)
Background Type 2 diabetes mellitus is a major public health problem worldwide. Nonadherence to lifestyle modifications in individuals with type 2 diabetes poses a great problem. Objective This study assessed magnitude and factors associated with nonadherence to diet and exercise. Methods An institution-based cross-sectional study was conducted on 302 type 2 diabetic patients at Asella Referral and Teaching Hospital of Arsi University. The data were collected via structured questionnaire. Multivariate logistic regression was used to determine the effects of independent variables on nonadherence to diet and exercise recommendations. Results Of the individuals in the study, 247(81.8%) patients did not follow the exercise recommendations, and 157(52%) patients did not follow the diet recommendations for type 2 diabetes. Duration since diagnosis > 5 years (AOR = 2.1, 95% CI [1.18–3.36]), doctors’ advice (AOR = 2.3, 95% CI [1.24–4.47]) and family history of DM (AOR = 4.3, 95% CI [2.55–7.29]) were independent determinants of nonadherence to dietary recommendations. Similarly, female sex (AOR = 3.6, 95% CI [1.60–8.60]), duration > 5 years since the diagnosis (AOR = 2.1, 95% CI [1.03–4.43]) and educational status attending only primary school (AOR = 3.33, 95% CI [1.33–8.34]) and only reading and writing or illiteracy (AOR = 6.7, 95% CI [1.86–24.29]) were independently associated with nonadherence to the exercise recommendation of type 2 diabetes patients. Conclusions Overall, in our study, many patients were nonadherent to diet and exercise recommendations. Female patients and patients who attended primary school or less and > 5 years since diagnosis were more likely to be nonadherent to exercise. The determinants of diet nonadherence were a lack of doctors’ advice, > 5 years since diagnosis and a lack of family history.